T-Shirt Design and Development for Amannah Collection Home Industry using Kano Model and Quality Function Deployment - Rizky Riza Putri; Andrean Emaputra; Cyrilla Indri Parwati; Ellyawan Setyo Arbintarso; Toto Rusianto (Institut Teknologi Dirgantara Adisutjipto, 2026)
Amannah Collection is a local business located in Boyolali, Central Java, Indonesia. It offers a variety of products, including T-shirts, jackets, and sports uniforms. However, production at the home industry has decreased and has not reached the target. To address these challenges, this study aims to develop products for Home Industry Amannah Collection that meet customer needs. This research was conducted using the KANO model to generate creative ideas and the QFD method to prioritize them. The study used the Kano questionnaire with 105 respondents. According to the KANO model, four attributes are classified as attractive: a dark black base color, short sleeves, a plain design, and a small-image screen-printed design. Meanwhile, using the QFD method, seven priority attributes are identified: T-shirts with a dark base color, simple designs, screen printing on only one side (front), neat and durable stitches, sizes that match customer measurements, materials that absorb sweat easily, and designs featuring image screen printing. This research aims to serve as a foundation for Amannah Collection to better understand customer needs, thereby increasing customer satisfaction and sales, as well as demonstrating the application of the Kano model in the apparel industry.